Kompatibilitas dan Efektifitas Fungi Mikorisa Arbuskula (FMA) terhadap Kacang Komak (Dolichos lablab L) - Sidqi Zaed Z.M.; Gita Pawana; Slamet Supriyadi (Agrovigor, 2008)
Besides, low nutrient availability  the problem in  dry land of Madura  is  the conflict  of land use  for food crops and  forage  production. Overcoming the problem  a program that  unite agriculture and husbandry activities is needed.  The objective of this research was to find out the most compatible and effective isolate of AMF on hyachinth bean (Dolichos lablab L)  as a forage legume.  The AMF which were   Gigaspora sp, Glomus sp, Glomus manihotis, Acaulospora sp dan Entrophosopra sp  were  planted beneath the bean seeds in polybag and   the plants were managed in a green house in optimal condition. The result showed that among isolates of arbuscular micorrhizal fungi, Gigaspora sp. greatly influenced growth and yield of biomass of hyachinth bean (Dolichos lablab L) indicating dependency of the plant to the fungus.  It is concluded that Gigaspora sp is the most compatible isolate for legume of hyachinth bean (Dolichos lablab L).